Negotiating Sharīʿah and Customary Law: Legal Pluralism in Familial Relationships among the Suku Anak Dalam in Jambi - Yanti, Illy; Yuliatin, Yuliatin; Mahmudah, Siti; Mahluddin, Mahluddin; Larasati, Yuniar Galuh (Journal of Islamic Law, 2025)
This article explores how the Suku Anak Dalam (SAD) community resists the application of Islamic law in family matters, specifically in the determination of dower (mahr), the management of joint property, and the distribution of inheritance. While most SAD members have formally converted to Islam, their legal practices remain rooted in a matrilineal customary system passed down through generations. Challenging prevailing scholarly emphasis on integrative frameworks between Islamic law and local custom, this study demonstrates that, in the SAD context, resistance emerges when elements of Islamic jurisprudence (fiqh) clash with the community’s socio-cultural structure and shared values. Using a socio-legal approach and qualitative methods, the research draws on in-depth interviews with seven key informants, including a religious leader, the tumenggung (tribal chief), customary elder, community facilitator, subdistrict head, and SAD community members. The findings reveal a persistent orientation toward collective female authority: mahr is determined by the bride’s maternal kin group; joint property, upon divorce, is granted entirely to the wife; and inheritance follows a strictly matrilineal line. Rather than rejecting Islamic law on theological grounds, this resistance reflects a form of public reasoning grounded in ancestral consensus. The study highlights the importance of interpreting Islamic law through contextual, dialogical, and adaptive lenses—particularly within societies shaped by legal pluralism. [Artikel ini mengkaji bentuk-bentuk resistensi yang muncul dalam komunitas Suku Anak Dalam (SAD) terhadap penerapan hukum Islam dalam ranah hukum keluarga, khususnya terkait penetapan mahar, pengelolaan harta bersama, dan pembagian warisan. Meski secara formal mayoritas anggota komunitas SAD telah memeluk Islam, praktik hukum yang dijalankan tetap berpijak pada sistem hukum adat matrilineal yang diwariskan lintas generasi. Berbeda dari kecenderungan literatur sebelumnya yang menekankan model integratif antara syariah dan adat, studi ini justru menunjukkan bahwa dalam konteks SAD, resistensi muncul ketika ketentuan-ketentuan fikih dianggap tidak sejalan dengan struktur sosial dan nilai-nilai kolektif komunitas. Dengan pendekatan sosio-legal dan metode kualitatif, penelitian ini mengumpulkan data melalui wawancara mendalam dengan tujuh informan kunci: tokoh agama, tumenggung (kepala suku), pemimpin adat, pendamping komunitas, pejabat lokal, dan anggota komunitas SAD. Temuan utama memperlihatkan bahwa praktik hukum keluarga di komunitas ini lebih menekankan otoritas kolektif perempuan, tercermin dari penentuan mahar oleh keluarga pihak ibu, pengalihan penuh harta bersama kepada istri setelah perceraian, serta sistem pewarisan yang mengikuti garis keturunan perempuan. Artikel ini berargumen bahwa resistensi tersebut bukan merupakan penolakan teologis terhadap hukum Islam, melainkan lahir dari penalaran publik yang bertumpu pada konsensus adat. Temuan ini menegaskan pentingnya pendekatan hukum Islam yang lebih kontekstual, dialogis, dan responsif terhadap pluralitas hukum dalam masyarakat adat.]